PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA SERENITY ECO GUESTHOUSE AND YOGA, CANGGU - Ni Rai Aditya Putri; I Wayan Mendra; Yenny Verawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Performance is the result of work both in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. The success of an organization/company depends on the performance of the individual or in other words the performance of the individual will contribute to the company. This study aims to test and obtain empirical evidence of the influence of leadership style, compensation and workload on employee performance at Serenity Eco Guesthouse and Yoga, Canggu. The population of this study is employees of Serenity Eco Guesthouse and Yoga, Canggu. The sample of this study was as many as 40 employees. Data analysis using multiple linear regression analysis techniques to answer problem formulations with the help of SPSS programs. The results showed that leadership style, compensation and workload had a positive and significant effect on employee performance at Serenity Eco Guesthouse and Yoga, Canggu. Further research can develop this research by using other variables in theory have an influence on employee performance